Semiotic Analysis of Positive Interpersonal Communication Behavior in The Web Series Film "Setan Taubat" - Ikhsan, Yuan Jauhari; Adiprabowo, Vani Dias (SOURCE : Jurnal Ilmu Komunikasi, 2024)
A web series is a serialized program similar to television shows, but the difference is that it is distributed through electronic media. In 2020, a popular YouTube content creator in Indonesia, along with their team, launched a web series titled "Setan Taubat." The web series revolves around positive activities during the holy month of Ramadan and tells the story of a successful hijab entrepreneur who has a supernatural friend named Becir. Many new developments in the storyline pique the curiosity of the audience, and the series conveys positive messages and behaviors. Verbal messages are emphasized in this web series. This research aims to analyze the forms of positive interpersonal communication behavior in the web series "Setan Taubat" using Charles Sanders Pierce's semiotics theory, which categorizes signs based on symbols, objects, and interpretants known as the meaning triangle. The research approach utilized is qualitative and descriptive to construct the meaning of messages in the web series "Setan Taubat" and comprehend the phenomenon by describing it through words. Additionally, the study employs semiotic analysis methods. Primary data collection is conducted through observation of the web series, and secondary data is obtained from documentation and literature review. The research results indicate that the web series "Setan Taubat" contains forms of positive interpersonal communication behavior as identified through Charles Sanders Pierce's semiotic analysis. Positive communication behavior that supports interpersonal communication includes openness, positive behavior, supportive behavior, empathy, and equality. Examples of attitudes include care, wisdom, responsibility, and others. These behaviors can be observed through the data findings presented in the research.